AB0212 Endothelin-1 and Serum from Systemic Sclerosis Patients Promote the Induction of Macrophage M2 Phenotype in Vitro. (9th June 2015) - Soldano, S.; Paolino, S.; Sulli, A.; Brizzolara, R.; Pizzorni, C.; Seriolo, B.; Montagna, P.; Cimmino, M.A.; Trombetta, A.C.; Cutolo, M.
Abstract : Background: Several immune-inflammatory cells, including endothelial cells and myofibroblasts, are involved in tissue damage that characterizes fibrotic diseases, including systemic sclerosis (SSc) (1). Alternative activated macrophages (M2) have also been implicated in the pathogenesis of fibrosis through the production of profibrotic molecules (i.e. fibronectin, metalloproteinases and TGFβ) (2). M2 are characterized by an increased expression of specific markers, primarily CD206 (mannose receptor1) and scavenger receptors (CD204 and CD163) (3). Endothelin-1 (ET-1) have been found in SSc to play a key role in fibrotic process, inducing both the myofibroblast activation and the overproduction of profibrotic extracellular matrix molecules (i.e. type I collagen and fibronectin) (4). Objectives: To investigate in vitro effects of serum from SSc patients and ET-1 in inducing the transition of cultured human macrophages into the profibrotic M2 phenotype. Methods: Human monocyte cells (THP1, 1x10 6 cells/ml) were activated into macrophages with phorbol myristate acetate (PMA, 25ng/ml) for 12hrs. Aliquots of these cultured macrophages were treated for 72 hrs with serum from SSc patients who fulfilled the new EULAR/ACR criteria for SSc diagnosis, and with serum from healthy subjects (HS) (5). Other macrophage aliquots were either untreated or treated for 72 hrs with ET-1 (100nM) or interleukin-4 (IL4, 10ng/ml), a known inducer of M2 phenotype (3). The expression of CD206 and CD204 was investigated by quantitative real time PCR (qRT-PCR) and immunocytochemistry (ICC). The expression of CD68 (marker of activated macrophages) was also investigated by ICC. Profibrotic mediator MMP-9 was analysed by zymography. Statistical analysis was performed by Mann-Whitney non-parametric U-test. Results: In cultured human macrophages, SSc serum determined a significant increase in CD206 and CD204 gene expression (p<0.05 for both) and induced the overproduction of MMP-9 compared to those cells treated with HS serum. The increased expression of both M2 markers was also confirmed by ICC. At the same time, ET-1 treatment induced a significant increase in the gene expression of CD206 and CD204 (p<0.05 for both), as well as the overproduction of MMP-9 in cultured human macrophage. The effects of SSc serum and ET-1 treatments were similar to those obtained by treatment with IL-4 in inducing the transition to the M2 phenotype markers. Conclusions: Preliminary results showed the ability of SSc serum (and its contents) to induce in vitro the polarization of human macrophages into the profibrotic M2 phenotype. ET-1, as one of the already assessed molecules increased in SSc serum, seems to induce very similar effects. References: Wei J et al. Autoimmun Rev 2011;10:267-75. Fairweather D et al. J Autoimmun 2009;33:222-30. Wynn TA et al. Nature 2013;496:445-53. Cutolo M et al. J Rheumatol 2015; 15(in press). van den Hoogen F et al. Arthritis Rheum 2013;65:2737-47. Disclosure of Interest: None declared